Discovering spatial dependence between experimental units of a fertilization field trial in an andean blackberry crop (Rubus glaucus Benth.) in Colombia - Gutiérrez Díaz, Joan Sebastián; Bolaños Benavides, Martha Marina; Bonilla Correa, Carmen Rosa; Cardona, William Andrés (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
The increasing domestic market (Colombia) and exports potential of the Andean blackberry (Rubus glaucus Benth.) is reected in a rapid growth of production, area sown and interest from the agrifood industry. All of these have made Andean blackberry production an important source of income for small and medium farmers. However, there is a knowledge gap regarding management of soil fertility for this crop in Colombia. The objective of this study was to address this knowledge gap. A nutritional experimental eld trial of Andean blackberry crop in Colombia eectively revealed the existence of spatial dependence for eciency of fertilization in experimental units. Such results have allowed the management improvement of fertilization to reduce or remove variability in fertilization eciency considering the spatial variation.